Kesadaran Beribadah Shalat Dhuhur Siswa Kelas X IPS dan Upaya Meningkatkannya di SMA Muhammadiyah 1 Palembang - Fadilatul Laily; Aset Sugiana (Journal of Islamic Education Research, 2020)
This research is intended to describe the religious consciousness of the praying dhuhr of students and the attempt to elevate it. This method of research involves qualitative work. Research data obtained from an Islamic religious teacher and student notebooks. The data analysis technique used that classifies, combines, interprets, and concludes. The study yielded the following conclusions: 1. The religious consciousness of praying dhuhr of students X IPS class at Muhammadiyah school 1 of Palembang was divided into a) a student whose consciousness was very good/good, b) a student of sufficient self-awareness and c) students who had poor spiritual awareness and still needed much improvement. The factors of student awareness in worship are due to a) Internal factor that is the factor comes from within the student; b). external factors such as family, school factors, and community factors. 2. Teacher PAI's role in raising awareness of worship the dhuhr student prayer, which is: a) acts as a teacher; b). acts as a tutor; c) acts as a leader; d) played the scientist; e) acts as a link; f) acting as a renewal. The role is performed by teachers supported by way: a) breeding; b. motivation; c. example; d. awareness; and e. surveillance.